Unique basite-metabasite structures of the Pobuzhsky ore mining region, their geological significance and ore-bearing prospects (by geophysical and geological data) - O.B. Gintov; V. Entin; S. V. Mychak; V. N. Pavlyuk; S. I. Guskov (Геофизический журнал, 2018)
The structure and prospects for ore content of three basite-metabasite massifs of the Pobuzhsky ore mining district — Bandurovsky, Troyan and Tarasovsky are considered using the example of the Tarasovska structure of the Middle Bug River of the Ukrainian Shield (USh). The assumption suggested by geologists back in 1990 about the geological and metallogenic uniqueness of these massifs is confirmed by the analysis of both regional geophysical surveys and materials of detailed geophysical works performed within the Tarasovska structure (basite-metabasite massif) in 2017 in connection with the geological-search works. It is shown that all three massifs are located within the epicentral regions of the largest gravity anomalies of the USh — Golovanevska and Bandurovska (68 and 49 mGal, respectively) — and they correspond to local maxima Dga with intensity up to 3—7 mGal against these anomalies. The most ancient enderbite-gneisses of the Yatransky and Khoshchevato-Zavalievsky blocks hosted the considered basite-metabasite massifs. The shape of the arrays is oval-concentric, that is why most geologists viewed them as brachisynclinal folds. According to the data of magnetometric and gravimetric surveys at a scale of 1 : 10,000 and small drilling volumes, the Tarasovska structure 3 ´ 5,5 km in size represents itself as a massif of apo-gabbroids — bipyroxene and amphibole-pyroxene crystal shales (in some places of norites and gabbros) of a clear oval shape surrounded by arcuate bands of skarnoids, garnet-bearing aluminous gneisses and calciphyres, bipyroxene and hypersthene crystal shales, among which for the first time manganese-containing gondites were encountered in the USh. Despite the presence of sedimentary cover overlapping the Tarasovska structure (Sarmatian and Quarterian deposits) of about 25—40 m thick, the massifs of apo-gabroids are distinguished on the background of the surrounding diurnal relief by distinct uplands with amplitude from several up to 10 m that supports the strength of these formations even on the background of enclosing granitoids. Geophysical, structural, petrological and geochemical data support the intrusive nature of the apogabbroids and the contact-metasomatic origin of their banding, rather than the brachisynclinal fold of metamorphosed sedimentary-volcanogenic rocks. The absence or very in-significant content of graphite gneisses in the framing structures of the Tarasovsky massif distinguishes these bands of gneisses, crystal shales and calciphyres from the sections of the Kosharo-Aleksandrovska and Khoshchevato-Zavalievsky suite of the Bug series with specific wide distribution of gneisses of graphite and biotite-graphite composition. The contact-metasomatic nature of the gneiss-crystal-shale-calciferous formations of the Tarasovo structure, as well as the possible metasomatic nature of the graphite and some other gneisses of the Middle Bug River, according to some researchers, raises the issue of the necessity of discussing and in-depth analysis of stratigraphic schemes of the Early Precambrian of the USh. The further direction of geological prospecting within the Tarasovska structure for apatite and titanium ores is discussed, and the most promising areas for the drilling of wells are also considered.